The prevalence of accidental awareness during general anaesthesia in obstetric patients undergoing caesarean section in Pelonomi Tertiary Hospital - Mofubelu, Sello Joseph (University of the Free State, 2017)
Abstract not available.
Keywords: Obstetric patients; Anaesthesia; Accident awareness; Pelonomi Tertiary Hospital; Caesarean section; Dissertation (M.Soc.Sc. (Anaesthesiology))--University of the Free State, 2017